2006
DOI: 10.1080/10245330600667526
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of factor VIII inhibitors in patients with hemophilia A in the north east of Iran

Abstract: This survey was conducted to evaluate coagulation factor VIII:C inhibitors among 102 hemophilia A patients from different cities of Khorasan province in north east of Iran in order to identify and characterize the pattern of inhibitor formation in these patients population. For this purpose, we randomly obtained plasma samples of 102 hemophilia A patients (44 patients with severe, 28 patients with intermediate and 30 patients with mild hemophilia A) and studied them using two tests: the APTT mix and Bethesda t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…[33] Nevertheless, these discrepancies may be related to differences in the study populations, management trends, and testing strategies. A study of 102 Iranian patients with hemophilia A (44 severe cases, 28 intermediate cases, and 30 mild cases) found that only 20 patients (19.6%) had inhibitors (11 severe cases, 5 intermediate cases, and 4 mild cases) [34] ; these findings are similar to our present findings. A large Indian study of 1285 patients with hemophilia A found that only 6.07% of the patients had inhibitors, although there were remarkable regional variations (the highest prevalence was 20.99%).…”
Section: Discussionsupporting
confidence: 91%
“…[33] Nevertheless, these discrepancies may be related to differences in the study populations, management trends, and testing strategies. A study of 102 Iranian patients with hemophilia A (44 severe cases, 28 intermediate cases, and 30 mild cases) found that only 20 patients (19.6%) had inhibitors (11 severe cases, 5 intermediate cases, and 4 mild cases) [34] ; these findings are similar to our present findings. A large Indian study of 1285 patients with hemophilia A found that only 6.07% of the patients had inhibitors, although there were remarkable regional variations (the highest prevalence was 20.99%).…”
Section: Discussionsupporting
confidence: 91%
“…Although Nijmegen assay is the recommended method for inhibitor assay by the International Society of Thrombosis and Hemostasis, most Iranian coagulation laboratories use the Bethesda assay. 15,19 Owing to the large size of FVIII, and to some extent FIX, genes, and genetic diversity in these genes, molecular diagnosis is not routinely performed for diagnosis or carrier detection in Iran. Genetic analysis imposes high costs on patients and the healthcare system.…”
Section: Diagnosis Of Hemophilia In Iranmentioning
confidence: 99%
“…Nowadays, long-term survival of individuals with haemophilia has been improved noticeably that attributable to many factors including improved treatment regimens, but new concerns such as inhibitor autoantibody to coagulation factors and RBD have been emerged recently [10,11]. We also need new insights into the pathophysiology and also management of reduced bone density in bleeding disorders.…”
Section: Introductionmentioning
confidence: 96%